Cultivating the future: a vision for Willow Lake Student Farm - Brown, Carter (My University, 2025)
The disconnect between people and the environment, along with food insecurity issues, has caused a growing need for proper agricultural education and training opportunities. University campus farms are great examples of spaces where students and visitors can engage with both agriculture and their environment. At Kansas State University’s Willow Lake Student Farm there is a great opportunity to create the premier student farm that serves as a model for sustainable agriculture. This project aims to explore the many agricultural opportunities available and provide a plan to develop a premier student farm experience at Willow Lake Student Farm. This report examines the background and importance of sustainable and regionally-focused agricultural education, discusses the research methods used, evaluates five farm precedent sites and summarizes three key interviews used to gather information, and present a conceptual master plan for Willow Lake Student Farm.
Keywords: University campus farm; Student farm; Sustainable agriculture; Agricultural education; Farm master plan and visioning; Visitor experience